2003
DOI: 10.1124/dmd.31.7.945
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the in Vivo Interaction Between Midazolam and Macrolides Based on in Vitro Studies Using Human Liver Microsomes

Abstract: This article is available online at http://dmd.aspetjournals.org ABSTRACT:Clinical studies have revealed that plasma concentrations of midazolam after oral administration are greatly increased by coadministration of erythromycin and clarithromycin, whereas azithromycin has little effect on midazolam concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
106
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(112 citation statements)
references
References 24 publications
(40 reference statements)
6
106
0
Order By: Relevance
“…However, in these reports, under-predictions of DDIs for several drugs using reversible inhibition data were made, as a result of these compounds actually being irreversible inactivators of drug-metabolizing enzymes. For individual drugs, others have shown that DDIs caused by irreversible inactivation of P450 enzymes can be predicted (Kanamitsu et al, 2000a;Mayhew et al, 2000;Yamano et al, 2001;Ito et al, 2003;Wang et al, 2004;Venkatakrishnan and Obach, 2005;Galetin et al, 2006). In these reports, the investigators have used various values for the input parameters such as enzyme degradation rate constants de- FIG.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in these reports, under-predictions of DDIs for several drugs using reversible inhibition data were made, as a result of these compounds actually being irreversible inactivators of drug-metabolizing enzymes. For individual drugs, others have shown that DDIs caused by irreversible inactivation of P450 enzymes can be predicted (Kanamitsu et al, 2000a;Mayhew et al, 2000;Yamano et al, 2001;Ito et al, 2003;Wang et al, 2004;Venkatakrishnan and Obach, 2005;Galetin et al, 2006). In these reports, the investigators have used various values for the input parameters such as enzyme degradation rate constants de- FIG.…”
Section: Discussionmentioning
confidence: 99%
“…For mechanism-based inactivators, there have been some reports describing the prediction of in vivo DDIs, particularly for CYP3A (Kanamitsu et al, 2000a;Mayhew et al, 2000;Yamano et al, 2001;Ito et al, 2003;Wang et al, 2004;Galetin et al, 2006), as well as one analysis for CYP2D6 . Compared with reversible inhibition, there are some added complexities regarding the prediction of DDIs from inactivation data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main mechanism underlying interactions between macrolide antibiotics and statins is often ascribed to the inhibition of the drugmetabolizing enzyme CYP3A4. [43][44][45] For this reason, the US Food and Drug Administration (FDA) currently warns against the co-administration of strong CYP3A4 inhibitors, including clarithromycin, with CYP3A4-metabolized 46 However, the inhibition of CYP3A4 cannot explain the increased risk of statin toxicity observed in our study, because we examined interactions with statins not metabolized by CYP3A4.…”
Section: Discussionmentioning
confidence: 46%
“…To specifically address this question, in vitro-in vivo extrapolations were conducted to determine the magnitude of competitive and time-dependent inhibition associated with plasma M2 levels. Conceptually, time-dependent reductions in parent drug CL resulting from inhibitory metabolites could be predicted in a manner analogous to predicting DDIs resulting from coadministered competitive and mechanism-based inhibitors (Mayhew et al, 2000;Ito et al, 2003;Brown et al, 2006). A key parameter used in these models is the inhibitor concentration at the enzyme active site (I u ) (Mayhew et dmd.aspetjournals.org these concentrations cannot be directly measured, surrogates based on plasma levels are often used.…”
Section: Discussionmentioning
confidence: 99%